Safety assessment of the substance 2,2′‐oxydiethylamine for use in plastic food contact materials - EFSA Panel on Food Contact Materials (FCM),; Claude Lambré; Riccardo Crebelli; Maria deSilva; Konrad Grob; Evgenia Lampi; Maria Rosaria Milana; Marja Pronk; Mario Ščetar; Georgios Theodoridis; Els Van Hoeck; Nadia Waegeneers; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Contact Materials assessed the safety of 2,2′‐oxydiethylamine, which is intended to be used at up to 14% w/w as a monomer along with adipic acid and caprolactam to make polyamide thin films intended for single use, in contact with all types of food under all conditions of time and temperature. Specific migration of 2,2′‐oxydiethylamine was tested from a polyamide film in water and was below the limit of quantification (LOQ) of 0.015 mg/kg. Migration of impurities has been estimated pro‐rata. Migrating oligomers were identified and semi‐quantified in 10% ethanol, 3% acetic acid and olive oil. Considering the measured migration and the virtual presence at the LOQ of the oligomers below 1000 Da containing the substance, the estimated migration of these oligomers would be 1.042 mg/kg. Genotoxicity studies were performed on the substance and on 1‐oxa‐4,11,18‐triazacycloeicosane‐5,10,17‐trione and 1‐oxa‐4,11,18,25‐tetraazacycloheptacosane‐5,10,17,24‐tetraone. (Q)SAR analyses were provided on the oligomers of higher molecular masses. Based on these data, the Panel excluded genotoxicity concerns for the substance and its oligomers. From a 90‐day toxicity study on the 1‐oxa‐4,11,18‐triazacycloeicosane‐5,10,17‐trione, the Panel identified a NOAEL of 1040 mg/kg bw per day. Based on their physico‐chemical properties and experimental data, the Panel considered the potential for accumulation in humans of the oligomers containing the substance of no concern. The Panel concluded that the substance is not of safety concern for the consumer if it is used as a comonomer with 99.6% minimum purity at up to 14% w/w to manufacture polyamide films (maximum thickness: 25 μm) and intended to be used in contact with all types of foods, except infant formula and human milk, at all time and temperature conditions. The migrations of the substance and of the oligomers below 1000 Da containing the substance should not exceed 0.05 and 5 mg/kg food, respectively.